Enhanced adsorption of tetrabromobisphenol a (TBBPA) on cosmetic-derived plastic microbeads and combined effects on zebrafish. (June 2020) - Yu, Yunjiang; Ma, Ruixue; Qu, Han; Zuo, You; Yu, Ziling; Hu, Guocheng; Li, Zongrui; Chen, Haibo; Lin, Bigui; Wang, Bin; Yu, Gang
Abstract: Microplastics (MPs) pollution and its potential environmental risks have drawn increasing concerns in recent years. Among which, microbeads in personal care and cosmetic products has becoming an emerging issue for their abundance as well as the knowledge gaps in their precise environmental behaviors in freshwater. The present study investigated the sorption process of tetrabromobisphenol A (TBBPA), the most widely applied and frequently encountered flame retardant in aquatic environments, on two sources of polyethylene (PE) particles (pristine PE particles and microbeads isolated from personal care and cosmetic products). Significantly enhanced adsorption capacity of microbeads was observed with up to 5-folds higher than the pristine PE particles. The sorption efficiency was also governed by solution pH, especially for the cosmetic-derived microbeads, indicating the strong adsorption of TBBPA on PE was dominated by both hydrophobic and electrostatic interactions. Additionally, combined effects on redox status of zebrafish were evaluated with two environmental relevant concentrations of PE particles (0.5 and 5 mg L −1 ) using integrated biomarker response (IBR) index through a 14-d exposure. Co-exposure induced significant antioxidative stress than either PE or TBBPA alone when exposed to 0.5 mg L −1 of MPs. After 7-d depuration, the IBR value for combination treatments [TBBPA + PE (L)] was 3-fold compared with that in MP-free groups, indicating the coexistence might exert a prolonged adverse effects on aquatic organisms. These results highlight the probability of risk from microbead pollution in freshwater, where toxic compounds can be adsorbed on microbeads in a considerable amount resulting in potential adverse effects towards aquatic organisms. Graphical abstract: Image 1 Highlights: Adsorption of flame retardant on cosmetic-derived PE microbeads was first studied. Enhanced sorption capacity was remarkable for cosmetic PE microbeads. Significantly increased redox stress in zebrafish in microplastic present exposure. Combined exposure exerted prolonged effects. Abstract : Adsorption of flame retardant on cosmetic microbeads was first studied. Remarkably enhanced sorption capacity on microbeads and redox stress in zebrafish were observed.